Influence of Acidic Soils on Growth and Nutrient Uptake of Cocoa (Theobroma Cacao L.) Varieties. Issue 17 (24th September 2020) - Dogbatse, Jerome Agbesi; Arthur, Alfred; Padi, Francis Kwame; Konlan, Sampson; Quaye, Amos Kojo; Owusu-Ansah, Frank; Awudzi, Godfred Kweku
ABSTRACT: Increasing soil acidity is one of the major factors limiting crop production in Ghana. Hence, identifying cocoa varieties that are well adapted to acidic soils and better extractors of important cocoa nutrients viz phosphorus (P) and potassium (K) is a suitable way to optimize the use of acidic soils to improve cocoa production. A 4 × 12 factorial in completely randomized design with four replications was used to evaluate 12 cocoa varieties grown in four acidic soils for the following traits: height, stem diameter, root length and volume, dry matter, and nutrient uptake. No significant varietal and soil effects for height and stem diameter were observed. T60/887 × CRG 8914 and PA 150 × EQ 3338 produced higher dry matter yields. Varieties had significantly longer roots and bigger root volumes in Samreboi series than in the other soils. Dry matter yields were highest in PA 150 × EQ 3338 and T60/887 × CRG 8914 across the soils. Absolute amounts of nitrogen (N) and P uptake were highest in PA 150 × PA 88 across the four soils, while K was highest in SPD cross. Nutrients uptake across the varieties was in the order N >  P > K in Nzima series and Samreboi series, and N > K > P in Wiawso series and Wacri series . The superiority of T60/887 × CRG 8914, PA 150 × EQ 3338, and PA 150 × PA 88 over the other varieties in terms of growth and nutrient uptake suggest they may be desirable for planting on acidic soils.